A187 CHOLESTATIC LIVER DISEASE AND BRAIN DYSFUNCTION: ROLE OF THE ARYL HYDROCARBON RECEPTOR. (26th February 2020) - Mathews, A J; Vicentini, F; Swain, L; Swain, M; Sharkey, K A
Abstract: Background: Cholestatic liver disease is associated with immune-mediated inflammatory liver injury. This disorder is also associated with brain dysfunction and behavioural changes, notably fatigue, depression and social withdrawal. The mechanisms leading to these central nervous system abnormalities are unknown, however, they are associated with neuroinflammation. Microglia and astrocytes are two glial populations that play key roles in neuroinflammation. Activated glia display morphological changes, secrete cytokines, and mediate electrophysiological changes, altering the normal functioning of the brain. The aryl hydrocarbon receptor (AhR) is a transcription factor involved in the immune response. AhR is present on glia and its' activation has been shown to reduce neuroinflammation. The role of the AhR in cholestatic liver disease has yet to be examined. Aims: To study the function of the AhR in a model of cholestic liver disease. We will test the hypothesis that activation of AhR in the brain will reduce neuroinflammation and behavioral deficits observed in cholestatic mice. Methods: Male C57Bl/6J mice had cholestasis induced by bile duct ligation (BDL); comparisons were made to sham-operated controls. Mice were tested for social interaction with a 4-week old juvenile in their home cage and the number of social interaction attempts quantified. Next, mice were euthanized, brains were removed and processed for immunohistochemistry. Brain sections were stained for markers of microglia (IBA-1) and astrocytes (GFAP). Microglia were counted and astrocyte activation was qualitatively assessed. PCR was used to quantify gene expression of AhR and its downstream gene targets (eg. CYP1A1) in mice that recived treatment with beta-napthoflavone (BNF), an AhR agonist, or in vehicle treated controls. Results: BDL mice made significantly fewer attempts to interact with the juvenile as compared to controls (P<0.05). We also observed a significant increase in IBA-1 immunoreactive cell numbers in both the CA1 region of the hippocampus and the hypothalamic paraventricular nucleus (PVN, P<0.05). BDL mice also displayed marked increases in GFAP+ staining in the PVN, but not the CA1, in contrast to sham controls. Lastly, we found that BNF significantly upregulated CYP1A1 (P<0.05) in the liver and prefrontal cortex of mice. We are currently examining whether BNF can reduce neuroinflammation and improve decreased social interaction in cholestatic mice. Conclusions: Cholestatic liver damage was associated with impaired social behavior. Further, glial activation, an indicator of neuroinflammation was increased in components of the limbic system associated with the response to stress, learning, and memory. Future experiments will address whether activation of the AhR will ameliorate neuroinflammation and behavioral changes observed in mice with cholestatic liver injury. Funding Agencies: CCC, CIHR